Penyeimbangan Lintasan Produksi Dengan Metode Heuristik (Studi Kasus PT. XYZ Makassar) - S Saiful; Mulyadi Hambali; Tri Muhadi Rahman (Department Industrial Engineering, University of Muhammadiyah Malang, 2014)
PT XYZ is one of the company which refers to furniture industries sector. The problem which faced by this company is unbalance of the production line which is caused by the unequal of work responsibility distribution in each work station. This problem caused the performance of line balance doesn’t work properly. To solve this problem we need to do the line balancing of production line. It can be done by line balancing methode that assigns a number of work which is related in one production line until each work station has efficient time which is not more than the cycle time of the work station. Line balancing methode that used is heuristic methode which is devided into ranked positional weight methode, large candidate rule methode, and region approach methode. From those three heuristic methode that used as solution of line balancing, there was improvement happenned with the same value in doors of production line. Line efficiency increased into 94,07% from 62,71% at the beginning condition. Balance delay increased into 5,92% from 37,28% at the beginning condition. The idle time descreased into 12,39 minutes from 116,87 minutes at the beginning condition. The smoothness index descreased into 7,44 from 64,67 at the beginning condition.